50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-534
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Surface Catalysis for Graphite Exposed to High-Enthalpy Nitrogen Flow

Abstract: The high temperatures on a hypersonic vehicle surface caused by heat loads encountered during (re-)entry through a planetary atmosphere require a reliable Thermal Protection System (TPS) that makes a good understanding of the physical and chemical processes essential for its design. Surface catalysis is a crucial chemical process that directly impacts aerothermal heating of the vehicle TPS. To study the effects of this process, a binary catalytic atom recombination model is implemented in a computational fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is concluded that the nonuniform inlet profile does not significantly affect the solution. The results for the study are discussed in [18,46]. An assumption of chemical equilibrium of the nitrogen gas mixture at the ICP torch exit is used to calculate its composition in these simulations, as experimental data at the exit are not available.…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that the nonuniform inlet profile does not significantly affect the solution. The results for the study are discussed in [18,46]. An assumption of chemical equilibrium of the nitrogen gas mixture at the ICP torch exit is used to calculate its composition in these simulations, as experimental data at the exit are not available.…”
Section: Resultsmentioning
confidence: 99%
“…The exit of the ICP torch is the inlet to the test chamber of the facility flow where the sample is tested. Previous studies 8,9 examined the effects of surface catalysis and the nature of the flowfield in the ICP torch facility for graphite exposed to high-enthalpy nitrogen flow. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 8, the surface catalysis effects were accounted for by using a simplified catalytic atom recombination model where the recombination of nitrogen atoms to molecules due to catalysis was investigated. It was shown that the temperature in the boundary layer is not affected by surface catalysis whereas it strongly affects the boundary layer gradients of species concentration, and heat transfer to the surface.…”
Section: Introductionmentioning
confidence: 99%